FRI0280 Efficacy and Safety of Tocilizumab as First Line Therapy in Patients with Recent Polymyalgia Rheumatica (PMR): Results of the First Longitudinal Prospective Study (Tenor). (9th June 2015) - Devauchelle, V.; Berthelot, J.-M.; Cornec, D.; Renaudineau, Y.; Marhadour, T.; Jousse-Joulin, S.; Querellou, S.; Guarrigues, F.; De Bandt, M.; Gouillou, M.; Saraux, A.
Abstract : Objectives: To evaluate efficacy and safety of tocilizumab as first line therapy in patients with recent Polymyalgia Rheumatica (PMR). Methods: Patients with recent PMR fulfilling the Chuang criteria, with a disease duration of less than 12 months, an active disease (PMR-AS>10) and glucocorticoids (GCs) naives were included in the TENOR study (Tolerance and Efficacy of tocilizumab iN pOlymyalgia Rheumatica). Patients with suspected giant cell arteritis were excluded. They were treated with tocilizumab infusions (week 0, 4 and 8) without GCs (period 1) and then by GCs from week 12 to week 24 (period 2). During period 2, GCs were prescribed according to the PMR-AS at week 12: Patients with PMR-AS ≤10 were treated by low dose (0.15mg/kg) whereas those with PMR-AS>10 received a classical dose (0.30 mg/kg). Treatment rescue was possible at each visit in cas of PMR-AS>15.All patients benefited from standardized radiographs, ultrasound, TEP scan and MRI of pelvic and ankle girdle. Primary endpoint was the response to tocilizumab based on PMR-AS ≤10 at week 12. Secondary endpoints were 1- PMR-AS response at week 24 and 2- GC sparing effect (cumulative dosage at week 24 in our treated patients versus virtual patients treated by classical reduction of corticosteroid dosage started at 0.30 mg/kg. 3-Imaging improvement (ultrasound, TEP scan and MRI of pelvic). Results: 20 patients were included and treated, 13 females and 7 males with a median aged of 67 years (IQR: 62.0-72.5). At inclusion, median PMR-AS was 36.9 (IQR: 30.5-43.9); 90% (18/20) of the patients had girdle and pelvic pain. At week 12, all patients (100%) were in remission at W12 according to the PMR-AS. All were included in the low dose corticosteroid group. Median PMR-AS at week 12 and 24 were respectively 4.5 (IQR: 3.2-6.8) p<0.001 and 0.95 (IQR: 0.4-2) p<0.001. Visual analogic scale for fatigue, pain and global activity were also statistically improved at week 12 and 24. No treatment rescue was necessary during period 1 or 2. During the period 2, all the patients received the low dose of GCs (0.15mg/kg/j).Tocilizumab induced a sparing corticosteroid effect, the cumulative doses of prednisone were respectively 1690.5mg (IQR: 1274.6-1871.8) in the virtual group versus 808.5 mg (IQR:673.3-866) in our treated patients (p<0.001).Concerning tolerance, three patients experienced severe events, two were related to tocilizumab. Most frequent adverse events were transient neutropenia and leucopenia reported in 3 and 5 patients. One patient received only one infusion of tocilizumab due to adverse event. Conclusions: Monotherapy with Tocilizumab have a major efficacy in recent PMR and allows a sparing corticosteroid effect. Disclosure of Interest: V. Devauchelle Grant/research support from: Chugai, J.-M. Berthelot: None declared, D. Cornec: None declared, Y. Renaudineau: None declared, T. Marhadour: None declared, S. Jousse-Joulin: None declared, S. Querellou: None declared, F. Guarrigues: None declared, M. De Bandt: None declared, M. Gouillou: None declared, A. saraux: None declared